Osteochondroma of the scapula - Alcantara, Marcela da Costa e Silva; Garcia, Tiago Severo; Miranda Junior, Hugo Mallmann de; da Cunha, Carol Fernandes Jerzewski Sotero (Clinical and Biomedical Research, 2014)
A 29 years old, female, presented with pain in the right dorsal and scapullary region after excruciating physical effort. Ultrasonography was performed and it was reported an anechoic collection with internal debris, measuring 10.0 x 8.0 x2.7 cmin diameters. After this result it was conducted a Magnetic Resonance Imaging (MRI) exam of the chest, with gadolinium injection and it was identified soft tissue injury, lying between the latissimus dorsi and the rib cage, without infiltration of the nearby fat tissue. It was seen bone proliferation in the medial aspect of the body of the scapula, with regular borders, in contact with the soft tissue lesion, that motivate an evalution with Multidetector Computer Tomography (MDCT) (figs. 1, 2 and 3). In this MDTC, it was identified bone lesion showing continuity of cortical and medullary bone, characteristic of osteochondroma. The anatomo-pathologic (AP) analysis demonstrated the presence of osteochondroma without signs of malignancy.